Measurement of Social Norms Affecting Modern Contraceptive Use: A Literature Review. Issue 4 (22nd November 2017) - Costenbader, Elizabeth; Lenzi, Rachel; Hershow, Rebecca B.; Ashburn, Kim; McCarraher, Donna R.
Abstract: As a critical building block to developing social norms interventions to support healthy family planning and other reproductive health behaviors, we conducted a literature review to identify and evaluate social norm measures related to modern contraceptive use. Of 174 articles reviewed in full, only 17 studies met our criteria for inclusion. Across these articles, no single measure of norms was used in more than one study; failure to specify the boundaries of who was engaging in and influencing the behaviors of interest contributed to the variation. Most of the studies relied on cross‐sectional data, only included condom use as their contraceptive use outcome, used individual‐ or interpersonal‐level behavior change theories rather than social‐level theories, and assumed a reference group, all of which limit the quality of the norm measures. We make several recommendations to bring greater consistency and comparability to social norm measures.